PROGRAM BINA BACA TULIS AL-QUR`AN DALAM MENGATASI RENDAHNYA KEMAMPUAN MEMBACA AL-QUR`AN PESERTA DIDIK DI SDN SITUGADUNG II KABUPATEN TANGERANG - Lulu Nadillah; Diah Mutiara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The ability to read the Qur’an is a fundamental skill that must be mastered by students, especially at the elementary school level. However, in reality, many students still have low ability in reading the Qur’an, including recognizing hijaiyah letters, fluency, and accuracy in applying tajwid rules. This study aims to analyze the implementation of the Bina Baca Tulis Al-Qur’an (BTQ) program in overcoming students’ low reading ability at SDN Situgadung II, Tangerang Regency. This research uses a qualitative descriptive method. Data were collected through observation, interviews, and documentation involving school principals, teachers, and students. The results show that the BTQ program is implemented systematically, structured, and continuously using methods such as tilawati. The program has a positive impact on improving students’ ability to read the Qur’an, including fluency, accuracy, and confidence. Supporting factors include school support, teacher competence, and adequate facilities, while inhibiting factors include differences in students’ abilities and lack of parental guidance at home.